Apoptosis sel hepatosis sebagai akibat dari metabolisme alkohol - Nabilah Amirah Salsabila (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Alcohol, or what is called ethanol, is a psychoactive substance that can cause dependence. The prevalence of disorders due to alcohol use is 0.8% and the prevalence of alcohol dependence is 0.7% in men and women. In Lampung province, the percentage of alcohol use is quite high at 3.6% in Tanggamus district and 2% in South Lampung district. Alcohol can damage organs through the process of metabolism. The liver is an organ that has a large impact on the effects of alcohol, because alcohol metabolism occurs in the liver. One of its effects on the liver is apoptosis of hepatocyte cells in which hepatocyte cells are a functional unit of the liver. The main pathway for alcohol metabolism involves alcohol dehydrogenase (ADH), an enzyme that catalyzes the change of alcohol into acetaldehyde which is a reactive and highly toxic product. The microsomal enzyme oxidizing (MEOS) pathway involves the cytochrome P450 enzyme which can cause activation of reactive oxygen species (ROS) so that it causes oxidative stress, and cytokine release, such as tumor necrosis factor (TNF-α), which plays a role in necrosis and inflammation of the liver. Apoptosis of hepatocyte cells occurs because of a complex process of ethanol metabolism. The occurrence of apoptosis of hepatocyte cells is to eliminate hepatocyte cells that have been damaged by excessive alcohol consumption into the body.